2016
DOI: 10.1371/journal.pone.0149173
|View full text |Cite
|
Sign up to set email alerts
|

Cryptanalysis and Improvement of a Biometric-Based Multi-Server Authentication and Key Agreement Scheme

Abstract: With the security requirements of networks, biometrics authenticated schemes which are applied in the multi-server environment come to be more crucial and widely deployed. In this paper, we propose a novel biometric-based multi-server authentication and key agreement scheme which is based on the cryptanalysis of Mishra et al.’s scheme. The informal and formal security analysis of our scheme are given, which demonstrate that our scheme satisfies the desirable security requirements. The presented scheme provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 60 publications
0
62
0
1
Order By: Relevance
“…Besides, the protocol undergoes a faulty password modification procedure. Recently, Moon et al and Wang et al presented multiserver authenticated key agreement schemes that are found to be prone to many attacks according to our analysis. The Moon et al is prone to privileged insider attack, identity‐guessing attack, and session key disclosure, while Wang et al is found to be vulnerable to trace attack, session‐specific temporary information attack, key‐compromise information attack, and privileged insider attack.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Besides, the protocol undergoes a faulty password modification procedure. Recently, Moon et al and Wang et al presented multiserver authenticated key agreement schemes that are found to be prone to many attacks according to our analysis. The Moon et al is prone to privileged insider attack, identity‐guessing attack, and session key disclosure, while Wang et al is found to be vulnerable to trace attack, session‐specific temporary information attack, key‐compromise information attack, and privileged insider attack.…”
Section: Introductionmentioning
confidence: 80%
“…For comparing the costs, in Table 3, we represent hash operation with T h while overlooking XOR function 24 Wang et al 26 Moon et al 25 Ours due to its insignificant cost. Hence, considering the given performance analysis, we can infer that our proposed technique is more secure than Wang et al, Moon et al, and Chen and Lee schemes.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…The proposed protocol's security and performance comparison against related or analogous protocols [29][30][31][32][33]44,45 is presented in this section. The wrap-up of the comparison is outlined in Tables 3 and 4.…”
Section: Security and Performance Comparisonmentioning
confidence: 99%
“…reveals that proposed computation complexity is less than the complexity of the related schemes except Wang et al 44 But as it is evident from Table 3, the scheme of Wang et al is vulnerable to several severe attacks. Therefore, it can be concluded that proposed protocol is more robust and efficient in terms of computation complexity and security strength.…”
mentioning
confidence: 93%
“…Based on [21,22,23], the fuzzy extractor is given by two procedures (Gen, Rep). The mechanism of a fuzzy extractor consists of two procedures (Gen, Rep), which is demonstrated as:

Gen(BIO)〈〉R,P,

Repfalse(BIO*,Pfalse)=R if BIO* is reasonably close to BIO.

…”
Section: Preliminariesmentioning
confidence: 99%